2008
DOI: 10.3957/0379-4369-38.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in nitrogen and phosphorus concentrations in faeces from springbok in the Kalahari

Abstract: The nutritional status of springbok, Antidorcas marsupialis, in the Kalahari was assessed in four habitats and three seasons by means of faecal profiling. Habitat only had a significant effect on the faecal nitrogen concentration in the cold-dry season, whereas faecal phosphorus concentrations showed no significant differences across habitats within a season. Seasonal differences in faecal nitrogen and phosphorus concentrations were more pronounced than habitat differences. Both faecal nitrogen and phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…A comparison of fecal nutrition estimates among populations suggests that the nutritional concentration of forage ingested by herbivores in Etosha is similar to or better than what these species access in other savanna areas. Springbok in Etosha had similar quantities of fecal nitrogen and phosphorus to springbok in the Northern Cape (Mbatha and Ward 2006) and similar fecal nitrogen but higher phosphorus to springbok in the Kalahari (Stapelberg et al 2008). Fecal nitrogen and phosphorus levels recorded in elephants in Pilansberg, South Africa (Woolley et al 2009) were similar to those observed in this study.…”
Section: Seasonality Of Nutritionsupporting
confidence: 81%
“…A comparison of fecal nutrition estimates among populations suggests that the nutritional concentration of forage ingested by herbivores in Etosha is similar to or better than what these species access in other savanna areas. Springbok in Etosha had similar quantities of fecal nitrogen and phosphorus to springbok in the Northern Cape (Mbatha and Ward 2006) and similar fecal nitrogen but higher phosphorus to springbok in the Kalahari (Stapelberg et al 2008). Fecal nitrogen and phosphorus levels recorded in elephants in Pilansberg, South Africa (Woolley et al 2009) were similar to those observed in this study.…”
Section: Seasonality Of Nutritionsupporting
confidence: 81%
“…Furthermore, this study only analysed a small selection of the plant species consumed by springbok. In a study undertaken to assess the nutritional status and diet quality of springbok in the Kalahari by means of faecal profiling, it was found that the faecal N concentration of springbok in the Auob riverbed was not below the critical level required for sustenance of normal metabolic processes (Stapelberg et al 2008) indicating that springbok may have the ability to select the food plant species with adequate N contents during this season. In contrast to the nutrient analysis of the food plant species, the faecal analysis showed that the N concentration of faeces collected in the dunes was below the critical level for rumen fermentation in the cold-dry season.…”
Section: Crude Proteinmentioning
confidence: 98%
“…The FP, as an efficient marker of the P intake in sheep, was also observed by Mellado et al [61], with seasonal variations from 0.8% in autumn to 2.1% in spring, on dry matter basis. Studies in other ruminants such as springbok (Antidorcas marsupialis), blue wildebeest (Connochaetes taurinus) and goats (Capra aegagrus hircus), have also shown substantial changes in FP concentration according to the dry or rainy season in semi-arid grasslands [69,70]. The above equations to estimate nutrient intake in extensive grazing-sheep should be validated in different grassland types, since the type and number of consumed plants and the changes in nutrient concentration that they experience throughout their life cycle could affect these relationships.…”
Section: Faecal Nitrogen (Fn) Phosphorus (Fp) and 26-diaminomipelicmentioning
confidence: 99%